Self-assembled liquid crystal architectures for soft matter photonics - Ma, Ling-Ling; Li, Chao-Yi; Pan, Jin-Tao; Ji, Yue-E.; Jiang, Chang; Zheng, Ren; Wang, Ze-Yu; Wang, Yu; Li, Bing-Xiang; Lu, Yan-Qing (Light, science & applications, 2022)
Self-assembled architectures of soft matter have fascinated scientists for centuries due to their unique physical properties originated from controllable orientational and/or positional orders, and diverse optic and photonic applications. If one could know how to design, fabricate, and manipulate these optical microstructures in soft matter systems, such as liquid crystals (LCs), that would open new opportunities in both scientific research and practical applications, such as the interaction between light and soft matter, the intrinsic assembly of the topological patterns, and the multidimensional control of the light (polarization, phase, spatial distribution, propagation direction). Here, we summarize recent progresses in self-assembled optical architectures in typical thermotropic LCs and bio-based lyotropic LCs. After briefly introducing the basic definitions and properties of the materials, we present the manipulation schemes of various LC microstructures, especially the topological and topographic configurations. This work further illustrates external-stimuli-enabled dynamic controllability of self-assembled optical structures of these soft materials, and demonstrates several emerging applications. Lastly, we discuss the challenges and opportunities of these materials towards soft matter photonics, and envision future perspectives in this field. This paper reviews recent advances in self-assembled liquid crystalline architectures in terms of their fabrications, manipulations, as well as emerging applications.